Dietary camphene attenuates hepatic steatosis and insulin resistance in mice. (10th September 2013) - Kim, Sohee; Choi, Youngshim; Choi, Seoyoon; Choi, Yeji; Park, Taesun
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to investigate the protective effects of camphene on high‐fat diet (HFD)‐induced hepatic steatosis and insulin resistance in mice and to elucidate its mechanism of action. Design and Methods Male C57BL/6N mice were fed with a normal diet, HFD (20% fat and 1% cholesterol of total diet), or HFD supplemented with 0.2% camphene (CPND) for 10 weeks. Results Camphene alleviated the HFD‐induced increases in liver weight and hepatic lipid levels in mice. Camphene also increased circulating adiponectin levels. To examine the direct effects of camphene on adiponectin secretion, 3T3‐L1 adipocytes were incubated with camphene. Consistent with in vivo result, camphene increased adiponectin expression and secretion in 3T3‐L1 adipocytes. In HFD‐fed mice, camphene increased hepatic adiponectin receptor expression and AMP‐activated protein kinase (AMPK) activation. Concordant with the activation of adiponectin–AMPK signaling, camphene increased hepatic expression of fatty acid oxidation‐related genes and decreased those of lipogenesis‐related genes in HFD‐fed mice. Moreover, camphene increased insulin‐signaling molecules activation and stimulated glucose transporter‐2translocation to the plasma membrane in the liver. Conclusions These results suggest camphene prevents HFD‐induced hepatic steatosis and insulin resistance in mice; furthermore, these protective effects are mediated via the activation of adiponectin–AMPK signaling.